Kekuatan Dokumen Hibah Elektronik Pesakit Covid-19 Dalam Situasi Maradh Al-mawt Menurut Perundangan Islam - Wan Abdul Fattah Wan Ismail; Mohd Radzniwan A Rashid; Syahirah Abdul Shukor; Lukman Abdul Mutalib; Ahmad Syukran Baharuddin; Norma Jusof; Mohamad Aniq Aiman Alias (Academia Industry Networks, 2024)
Non-Indexed Publication